Priming With the Green Leaf Volatile (Z)-3-Hexeny-1-yl Acetate Enhances Salinity Stress Tolerance in Peanut (Arachis hypogaea L.) Seedlings - Tian, Shufei; Guo, Runze; Zou, Xiaoxia; Zhang, Xiaojun; Yu, Xiaona; Zhan, Yuan; Ci, Dunwei; Wang, Minglun; Wang, Yuefu; Si, Tong (Frontiers in Plant Science, 2019)
Green leaf volatiles play vital roles in plant biotic stress, however, their functions in plant responses to abiotic stress remain unclear. The aim of this study was to investigate the possible role of Z-3-Hexenyl Acetate (Z-3-HAC), a kind of the green leaf volatile, on alleviating salinity stress of peanut (Arachis hypogaea L.) seedlings and the underlying physiological mechanisms. One salt-sensitive and one salt-tolerant peanut genotypes were primed with 200 μM Z-3-HAC at the four-week old stage before they were exposed to salinity stress. Physiological measurements showed that the primed seedlings possessed higher relative water content, net photosynthetic rate, the maximal photochemical efficiency of photosystem II, activities of the antioxidant enzymes, and osmolytes accumulation under salinity conditions. Furthermore, the reactive oxygen species, electrolyte leakage, and malondialdehyde content in the third fully expanded leaves showed significantly lower than non-primed plants. Additionally, we found that application of Z-3-HAC increased the total length, surface area, and volume of the peanut roots under salinity stress. These results indicated that the green leaf volatile Z-3-HAC protects peanut seedlings against damage from salinity stress through priming for modifications of photosynthetic apparatus, antioxidant systems, osmoregulation, and root morphology.